SALIZATION AND AMENITIES OF SOIL RESOURCES - Mamanov Jalaliddin (Web of Journals Publishing, 2025)
This in the article of the soil salinity about information The soil is given . salinity that is in the soil to be processes and events, its fertility effect, Saline soils groups , types , soil salinity appearances and in national equivalents per 100 grams of soil expressible in the soil absorbed all cations sum Ca, Mg, Na, K, H2, NH 4 absorption capacity lari illuminated . From it outside Karakalpakstan Republic , Khorezm , Bukhara , Jizzakh , and Fergana of the regions reclamation cases having studied released statement Salted . soils following to the reasons according to appearance to be five for the reason according to explained.
Keywords: Soil layer, pore layer, soil salinity, soil erosion.